A double-layer coated oxide positive electrode composite material and preparation method thereof

By adopting a double-layer clad structure on the sulfide positive electrode of the lithium-ion battery, the clad layer is carbon and sulfide electrolyte, the interface problem of the lithium-ion battery is solved and the cycle life and rate performance of the battery is significantly improved.

CN115799511BActive Publication Date: 2025-02-18SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211464976.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-02-18
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

Interface problems in existing lithium-ion batteries lead to high impedance, immobilization of movable lithium ions and formation of lithium dendrites, resulting in memory capacity loss and battery failure.

Method used

The sulfide positive electrode composite material adopts a double-layer clad structure, the core is FeS2, the first clad layer is C, and the second clad layer is a sulfide electrolyte. The FeS2@C@Li6PS5Cl material is formed by in-situ chemical method to improve sulfide Interface stability between the positive electrode and the sulfide electrolyte.

Benefits of technology

It significantly reduces the interface impedance of the electrode electrolyte, reduces adverse reactions between the electrode and the electrolyte, and improves the cycle life and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799511B_ABST
    Figure CN115799511B_ABST
Patent Text Reader

Abstract

The present invention provides a double-layer coated sulfide positive electrode composite material and a preparation method thereof. The present invention constructs an in-situ chemically coated sulfide positive electrode material with a core-shell structure, and then grows a layer of sulfide electrolyte on the surface of the outer shell to enhance the interface stability between the sulfide positive electrode and the sulfide electrolyte in an all-solid-state lithium-ion battery. A sulfide FeS2 with excellent theoretical specific capacity is selected, and an FeS2@C structure is formed by an in-situ chemical method; a layer of sulfide electrolyte is chemically coated on the surface to form a double-layer coated FeS2@C@Li6PS5X material. Sulfide provides high specific capacity, and the nano-thick carbon material shell reduces the influence of elastic stress during charging and discharging, improves the conductivity of the composite material, and improves the rate performance and cycle stability of the material. At the same time, in-situ coating of a layer of sulfide electrolyte can improve the point-to-point interface contact problem between the composite nanomaterial and the sulfide electrolyte, and improve the ion transmission channel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and specifically to a double-layer coated oxide positive electrode composite material and a preparation method thereof, and in particular to a double-layer coated positive electrode composite material and a preparation method thereof and a high-performance sulfide all-solid-state battery. Background Art

[0002] Improving the lithium-ion conductivity of solid electrolytes (SEs) is an important direction for the development of all-solid-state lithium batteries (ASSLBs). Recent studies have shown that solving existing interface problems is more important than maximizing the conductivity of the electrolyte. The interface is the key to ASSLBs, and its characteristics directly affect the performance of the battery. Interfacial problems are caused by the physical and electrochemical properties of the materials, which can significantly increase the internal resistance of the ASSLB. As a result, interfacial problems may lead to high impedance, immobilization of mobile lithium ions, and the formation of lithium dendrites, etc., all of which can lead to significant storage capacity loss and ultimately battery failure. Therefore, it is crucial to form a good interface for efficient lithium-ion transport.

[0003] High interfacial resistance usually comes from a variety of factors, including poor physical interface contact between solids, space charge caused by chemical reactions and electrochemical reactions, and the formation of interfacial layers. In addition, metal oxides or metal sulfides are also widely studied lithium-ion battery materials. These materials have high lithium insertion capacity (>600mAh / g) and a lithium insertion potential close to that of lithium titanate. However, since these materials themselves have poor electrical conductivity, and during the charge and discharge process, the agglomeration and cracking of metal sulfide materials seriously affect the discharge capacity and cycle performance of the battery, and cannot meet the long cycle performance requirements of energy storage batteries, it greatly limits the application of metal oxide and sulfide materials in batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a double-layer coated sulfide positive electrode composite material and a preparation method thereof in view of the defects in the prior art.

[0005] The object of the present invention is achieved through the following solutions:

[0006] The first aspect of the present invention provides a double-layer coated sulfide positive electrode composite material, which is a double-layer coating structure, including a core FeS2, a first coating layer C, and a second coating layer sulfide electrolyte from the inside to the outside.

[0007] The positive electrode composite material selects FeS2 with excellent theoretical specific capacity as sulfide, forms a FeS2@C structure through an in-situ chemical method, and further chemically coats a layer of sulfide electrolyte on the surface of the structure to form a double-layer coated FeS2@C@Li6PS5Cl material. The sulfide electrolyte includes one of Li6PS5F, Li6PS5Cl, Li6PS5Br, and Li6PS5I, which is consistent with the electrolyte used in assembling solid-state batteries, preferably Li6PS5Cl, which has better compatibility when coated.

[0008] In a second aspect, the present invention provides a method for preparing a double-layer coated sulfide positive electrode composite material, the preparation method comprising the following steps:

[0009] Step 1, preparing Fe3C@C precursor by liquid phase mixing and calcination method;

[0010] Step 2, mixing the precursor with elemental sulfur and calcining to form FeS2@C nanomaterials;

[0011] Step 3: Add FeS2@C nanomaterials and sulfide electrolyte raw materials into a solvent, stir, remove the solvent, dry and calcine to obtain a double-layer coated sulfide positive electrode composite material.

[0012] Preferably, the preparation method of the Fe3C@C precursor in step 1 is specifically as follows: dissolving polyvinyl pyridine in deionized water to form a transparent solution; adding Fe(NO3)3·9H2O to the transparent solution to form a yellow-brown mixed solution under stirring and ultrasonic action, and obtaining the Fe3C@C precursor after drying and calcining.

[0013] Preferably, the ratio of polyvinyl pyridine to Fe(NO3)3·9H2O is 1-1.5 g: 3-5 mmol. The ratio of polyvinyl pyridine to deionized water is 1-1.5 g: 35-45 ml. The drying temperature is 60-80°C. The calcination temperature is 600-900°C, the time is 1-3 hours, and the heating rate is 4-6°C min -1 Calcination is carried out in an Ar / H2 gas stream. If the calcination temperature is too low, the target product cannot be generated, and if the calcination temperature is too high, the target product may be carbonized or the crystal phase may change.

[0014] Preferably, in step 2, the specific steps of mixed calcination are: placing the Fe3C@C precursor and elemental sulfur at different positions in the calcination container respectively, and placing the elemental sulfur upstream of the calcination container; then heating and cooling to room temperature to obtain FeS2@C nanomaterials.

[0015] Preferably, the mass ratio of Fe3C@C precursor to elemental sulfur is 1:3-1:5. The heating temperature is 200-700°C, the time is 2-5 hours, and the heating rate is 1-2°C min-1 Controlling the heating speed and ensuring slow heating can make the reaction more complete and more sufficient. The heating is carried out in an argon atmosphere. The heating container is a crucible.

[0016] Preferably, in step 3, the mass ratio of FeS2@C nanomaterial to sulfide electrolyte raw material is 8-9:1-2; preferably 85:15. The amount ratio of FeS2@C nanomaterial to solvent is 0.85g:20ml. The solvent is acetonitrile, which has better dispersibility in acetonitrile solution and has a lower boiling point, which is conducive to post-treatment of vacuum distillation.

[0017] Preferably, in step 3, the sulfide electrolyte Li6PS5X includes one of Li6PS5F, Li6PS5Cl, Li6PS5Br, and Li6PS5I, preferably Li6PS5Cl. The sulfide electrolyte raw material is composed of Li2S, P2S5, and LiX in a molar ratio of 5:1:2, and X is one of F, Cl, Br, and I.

[0018] Preferably, in step 3, the stirring temperature is 30-50°C and the stirring time is 18-38h. The drying temperature is 60-100°C and the time is 6-12h. The solvent is removed by distillation under reduced pressure.

[0019] Preferably, in step 3, the calcination temperature is 200-500°C and the time is 1-2h. The calcination temperature is preferably 260°C. If the reaction calcination temperature is too low, the reaction is insufficient; as the temperature increases, the grain size increases, which is conducive to the enhancement of densification. However, when the sintering temperature is too high, the irregular particles have a larger space due to the increase in size, which reduces the density. And when the temperature is too high, the anisotropic thermal expansion causes material stress, causing voids and cracks in the material. So that the mobility of lithium ions is limited by larger grain boundaries.

[0020] In a third aspect, the present invention also provides an application of the double-layer coated sulfide positive electrode composite material in the preparation of a sulfide all-solid-state battery positive electrode.

[0021] Preferably, the sulfide all-solid-state battery comprises a positive electrode sheet, a sulfide electrolyte and a negative electrode sheet. The sulfide electrolyte is one or more of Li6PS5X (X=F, Cl, Br or I); the active material of the negative electrode sheet is metallic lithium, lithium alloy, carbon series material, Si-containing carbon series material or olivine structure transition metal material. The all-solid-state battery is pressed in the order of positive electrode-electrolyte-negative electrode. The battery effectively improves safety, interface resistance, capacity, cyclability and rate capabilities.

[0022] Preferably, the positive electrode sheet is prepared by mixing and pressing the double-layer coated sulfide positive electrode composite material and the sulfide solid electrolyte. Premixing the positive electrode and the electrolyte in advance is conducive to sheeting and can maximize its charge and discharge efficiency during the charge and discharge process.

[0023] The double-layer coated sulfide positive electrode composite material and its preparation method of the present invention first construct an in-situ chemically coated sulfide positive electrode material with a core-shell structure, and then grow a layer of sulfide electrolyte on the surface of the outer shell to enhance the interface stability between the sulfide positive electrode and the sulfide electrolyte in the all-solid-state lithium-ion battery. FeS2 with excellent theoretical specific capacity is selected as the sulfide, and an FeS2@C structure is formed by an in-situ chemical method. A layer of sulfide electrolyte is further chemically coated on the surface of the structure to form a double-layer coated FeS2@C@Li6PS5X material.

[0024] The present invention performs in-situ electrolyte coating on the sulfide positive electrode, which is beneficial to the effective contact between the material and the electrolyte, and improves the point-to-point contact problem in the solid-state battery. The preparation method is relatively simple and does not require complex technology. Although the nano-thick carbon material shell can reduce the influence of unnecessary elastic stress during the charge and discharge process and improve the conductivity of the composite material, there are still certain limitations in the contact between solid particles. FeS2 has a very low electrical conductivity, and the use of sulfide electrolyte for direct coating will cause the overall positive electrode material to have very poor conductivity. The presence of the C coating layer is not only beneficial to buffering the volume effect during charge and discharge, but also beneficial to improving the conductivity of the positive electrode material and reducing the interface resistance.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The double-layer coated sulfide positive electrode composite material of the present invention, wherein FeS2 is a sulfide, can be used in sulfide all-solid-state batteries to provide high specific capacity.

[0027] (2) The nano-thick carbon material shell reduces the influence of unnecessary elastic stress during the charge and discharge process, improves the conductivity of the composite material, and improves the rate performance and cycle stability of the material.

[0028] (3) In situ coating with a layer of sulfide electrolyte can further improve the point-to-point interface contact problem between the composite nanomaterials and the sulfide electrolyte and improve the ion transport channel.

[0029] (4) The double-layer coated sulfide positive electrode composite material of the present invention is applied to sulfide all-solid-state batteries, which can significantly reduce the interface impedance of the electrode electrolyte and the adverse reaction between the electrode and the electrolyte, thereby improving the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0031] Figure 1 The first charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Example 1;

[0032] Figure 2 Cyclic test of an all-solid-state battery assembled from a double-layer coated positive electrode composite material prepared in Example 1;

[0033] Figure 3 The first charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Example 2;

[0034] Figure 4 Cyclic test of an all-solid-state battery assembled from a double-layer coated positive electrode composite material prepared in Example 2;

[0035] Figure 5 The first charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Example 3;

[0036] Figure 6 Cyclic test of an all-solid-state battery assembled from a double-layer coated cathode composite material prepared in Example 3;

[0037] Figure 7 The charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Comparative Example 1;

[0038] Figure 8 Cyclic test of an all-solid-state battery assembled from a double-layer coated positive electrode composite material prepared in Comparative Example 1;

[0039] Fig. 9 The charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Comparative Example 2;

[0040] Fig.10 Cyclic test of an all-solid-state battery assembled from a double-layer coated positive electrode composite material prepared in Comparative Example 2;

[0041] Fig.11 The charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Comparative Example 3;

[0042] Fig.12 This is a cycle test of an all-solid-state battery assembled with a double-layer coated positive electrode composite material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0043] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0044] In the present invention, in-situ coating of the shell protective material on the surface of the positive electrode active material is the main way to improve the battery performance. In short, the implicit requirements of the positive electrode shell coating material can be summarized as follows:

[0045] a) Chemical compatibility with cathode materials and sulfide solid electrolytes;

[0046] b) Alleviate the average charge and discharge volume effect to adapt to volume changes;

[0047] c) Diffusion barrier properties to prevent interdiffusion during high temperature processing;

[0048] The adverse reaction between the positive electrode material and the sulfide solid electrolyte, as well as the large solid-solid interface resistance, result in the performance of the sulfide all-solid battery not meeting the requirements. In order to solve this problem, an ultra-thin buffer layer can be coated on the surface of the positive electrode material to form a double-coated positive electrode composite material. The buffer layer is inserted between the coated positive electrode material and the sulfide electrolyte to reduce the interface resistance, and inhibit the adverse reaction between the positive electrode material and the sulfide electrolyte, thereby achieving the low resistance, high capacity, long life and other performance of the sulfide all-solid battery.

[0049] The assembly of sulfide all-solid-state batteries based on coated cathode materials includes:

[0050] The coated positive electrode material and the sulfide solid electrolyte material (20 mg in total) were mixed evenly at a ratio of 7:3 and pressed into a sheet as the positive electrode sheet; the sulfide electrolyte (100 mg) was pressed into a sheet; and finally assembled with the negative electrode sheet into a full battery. The full battery charge and discharge test conditions: 0.2C; the cycle test conditions: 0.5C.

[0051] Example 1

[0052] Step 1: Preparation of Fe3C@C precursor: 1.2 g polyvinyl pyridine was dissolved in 40 ml deionized water at room temperature to form a transparent solution, 3.5 mmol Fe(NO3)3·9H2O was added to the transparent solution, and a yellow-brown solution was formed under stirring and ultrasonic action. The obtained mixed solution was completely dried at 70°C, and then calcined in an Ar / H2 flow at 800°C for 1.5 hours, with a heating rate of 5°C min -1 , Fe3C@C material is obtained.

[0053] Step 2: Preparation of FeS2@C nanomaterials: The synthesized Fe3C@C and sublimed sulfur were placed at two locations of a quartz crucible at a mass ratio of 1:5, and the sublimed sulfur was placed upstream of the furnace. Then, the crucible was heated at 300°C in an argon atmosphere for 2 hours at a heating rate of 1°C min -1 , finally, cooled to room temperature to obtain FeS2@C.

[0054] Step 3, FeS2@C@Li6PS5Cl material was prepared as follows: the prepared FeS2@C (0.85 g) and 0.15 g of Li2S, P2S5, and LiCl with a molar ratio of 5:1:2 were added to 20 mL of acetonitrile. After stirring at 50°C for 24 hours, the acetonitrile solution was removed by vacuum distillation and dried at 80°C for 10 hours. Finally, the FeS2@C@Li6PS5Cl composite material was obtained by calcining at 260°C for 1 hour.

[0055] The prepared FeS2@C@Li6PS5Cl composite material was used as the positive electrode, the sulfide Li6PS5Cl was used as the electrolyte, and the In-Li alloy was used as the negative electrode to assemble an all-solid-state battery for electrochemical testing. Figure 1 As shown, the cycle test is as follows Figure 2 shown.

[0056] Example 2

[0057] This embodiment provides a double-layer coated sulfide positive electrode composite material, and the preparation method includes the following steps:

[0058] Step 1: Preparation of Fe3C@C precursor: 1.2 g polyvinyl pyridine was dissolved in 40 ml deionized water at room temperature to form a transparent solution, 3.5 mmol Fe(NO3)3·9H2O was added to the transparent solution, and a yellow-brown solution was formed under stirring and ultrasonic action. The obtained mixed solution was completely dried at 70°C, and then calcined in an Ar / H2 flow at 800°C for 1.5 hours, with a heating rate of 5°C min -1 . Fe3C@C material is obtained.

[0059] Step 2: Preparation of FeS2@C nanomaterials: The synthesized Fe3C@C and sublimed sulfur were placed at two locations of a quartz crucible at a mass ratio of 1:5, and the sublimed sulfur was placed upstream of the furnace. Then, the crucible was heated at 500°C in an argon atmosphere for 2 hours at a heating rate of 1°C min -1 , finally, cooled to room temperature to obtain FeS2@C.

[0060] Step 3, FeS2@C@Li6PS5Cl material was prepared as follows: the prepared FeS2@C (0.85 g) and 0.15 g of Li2S, P2S5, and LiCl with a molar ratio of 5:1:2 were added to 20 mL of acetonitrile. After stirring at 50°C for 24 hours, the acetonitrile solution was removed by vacuum distillation and dried at 80°C for 10 hours. Finally, the FeS2@C@Li6PS5Cl composite material was obtained by calcining at 260°C for 1 hour.

[0061] The prepared FeS2@C@Li6PS5Cl composite material was used as the positive electrode, the sulfide Li6PS5Cl was used as the electrolyte, and the In-Li alloy was used as the negative electrode to assemble an all-solid-state battery for electrochemical testing. Figure 3 As shown, the cycle test is as follows Figure 4 shown.

[0062] Example 3

[0063] This embodiment provides a double-layer coated sulfide positive electrode composite material, and the preparation method includes the following steps:

[0064] Step 1: Preparation of Fe3C@C precursor: 1.2 g polyvinyl pyridine was dissolved in 40 ml deionized water at room temperature to form a transparent solution, 3.5 mmol Fe(NO3)3·9H2O was added to the transparent solution, and a yellow-brown solution was formed under stirring and ultrasonic action. The obtained mixed solution was completely dried at 70°C, and then calcined in an Ar / H2 flow at 800°C for 1.5 hours, with a heating rate of 5°C min -1 . Fe3C@C material is obtained.

[0065] Step 2: Preparation of FeS2@C nanomaterials: The synthesized Fe3C@C and sublimated sulfur were placed at two positions of a quartz crucible at a mass ratio of 1:5, and the sublimated sulfur was placed upstream of the furnace. Then, the crucible was heated at 100°C in an argon atmosphere for 2 hours at a heating rate of 1°C min -1 , finally, cooled to room temperature to obtain FeS2@C.

[0066] Step 3, FeS2@C@Li6PS5Cl material was prepared as follows: the prepared FeS2@C (0.85 g) and 0.15 g of Li2S, P2S5, and LiCl with a molar ratio of 5:1:2 were added to 20 mL of acetonitrile. After stirring at 50°C for 24 hours, the acetonitrile solution was removed by vacuum distillation and dried at 80°C for 10 hours. Finally, the FeS2@C@Li6PS5Cl composite material was obtained by calcining at 260°C for 1 hour.

[0067] The prepared FeS2@C@Li6PS5Cl composite material was used as the positive electrode, the sulfide Li6PS5Cl was used as the electrolyte, and the In-Li alloy was used as the negative electrode to assemble an all-solid-state battery for electrochemical testing. Figure 5 As shown, the cycle test is as follows Figure 6 shown.

[0068] Comparative Example 1

[0069] This comparative example is basically the same as Example 1, except that uncoated FeS2 is used as the positive electrode. Sulfide Li6PS5Cl is used as the electrolyte and In-Li alloy is used as the negative electrode. An all-solid-state battery is assembled and electrochemical tests are performed. The first charge and discharge test is as follows Figure 7 As shown, the cycle test is as follows Figure 8 shown.

[0070] Comparative Example 2

[0071] This comparative example is basically the same as Example 1, except that FeS2@C is used as the positive electrode. Sulfide Li6PS5Cl is used as the electrolyte and In-Li alloy is used as the negative electrode. An all-solid-state battery is assembled and electrochemical tests are performed. The first charge and discharge test is as follows Fig. 9 As shown, the cycle test is as follows Fig.10 shown.

[0072] Comparative Example 3

[0073] This comparative example is basically the same as Example 1, except that the calcination temperature of the crucible in step 2 is 700°C. Sulfide Li6PS5Cl is used as the electrolyte and In-Li alloy is used as the negative electrode to assemble an all-solid-state battery for electrochemical testing. Fig.11 As shown, the cycle test is as follows Fig.12 shown.

[0074] Performance Testing

[0075] The all-solid-state battery assembled from the double-layer coated positive electrode composite materials prepared in Examples 1-3 and Comparative Examples 1-3 was subjected to electrochemical testing.

[0076] Test method:

[0077] The coated positive electrode material and the sulfide solid electrolyte material (20 mg in total) were mixed evenly in a ratio of 7:3 and pressed into a sheet as the positive electrode; the sulfide electrolyte (100 mg) was pressed into a sheet; and finally assembled with the negative electrode sheet into a full battery. The charge and discharge performance and cycle stability were tested. The charge and discharge test conditions were: 0.2C; the cycle test conditions were: 0.5C.

[0078] Test results see Figure 1-12The first charge and discharge test results of the all-solid-state battery assembled from the double-layer coated positive electrode composite material prepared in Example 1 are as follows: Figure 1 As shown; the cycle test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Example 1 is as follows Figure 2 As shown; the first charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Example 2 is as follows Figure 3 The cycle test results of the all-solid-state battery assembled from the double-layer coated positive electrode composite material prepared in Example 2 are shown in Figure 4 As shown; the first charge and discharge test of the all-solid-state battery assembled with the double-layer coated positive electrode composite material prepared in Example 3 is as follows Figure 5 The cycle test results of the all-solid-state battery assembled from the double-layer coated positive electrode composite material prepared in Example 3 are shown in Figure 6 As shown; the charge and discharge test results of Comparative Example 1 are as follows Figure 7 The cycle test results of Comparative Example 1 are shown in Figure 8 As shown; the charge and discharge test results of Comparative Example 2 are as follows Fig. 9 As shown; the cycle test results of Comparative Example 2 are as follows Fig.10 As shown; the charge and discharge test results of Comparative Example 3 are as follows Fig.11 The cycle test results of Comparative Example 3 are shown in Fig.12 shown.

[0079] The results show that the composite oxide positive electrode materials prepared in Examples 1-3 of the present invention are applied to sulfide all-solid-state batteries, which can significantly reduce the interface impedance of the electrode electrolyte and the adverse reaction between the electrode and the electrolyte, thereby improving the cycle life of the battery.

[0080] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.

Claims

1. A method for preparing a double-layer coated sulfide positive electrode composite material, characterized in that: The preparation method comprises the following steps: Step 1, preparing Fe3C@C precursor by liquid phase mixing and calcination method; Step 2, mixing the precursor with elemental sulfur and calcining to form FeS2@C nanomaterials; Step 3, adding FeS2@C nanomaterials and sulfide electrolyte raw materials into a solvent, stirring, removing the solvent, drying, and calcining to obtain a double-layer coated sulfide positive electrode composite material; The double-layer coated sulfide positive electrode composite material is a double-layer coating structure, which includes a core FeS2, a first coating layer C, and a second coating layer sulfide electrolyte from the inside to the outside, and the sulfide electrolyte includes one of Li6PS5F, Li6PS5Cl, Li6PS5Br, and Li6PS5I; The preparation method of the Fe3C@C precursor in step 1 is specifically as follows: dissolving polyvinyl pyridine in deionized water to form a transparent solution; adding Fe(NO3)3·9H2O to the transparent solution to form a yellow-brown mixed solution under stirring and ultrasonic action, and drying and calcining to obtain the Fe3C@C precursor; In step 2, the specific steps of mixed calcination are: placing the Fe3C@C precursor and elemental sulfur at different positions in the calcination container, and placing the elemental sulfur upstream of the calcination container; then heating and cooling to obtain the FeS2@C nanomaterial; The dosage ratio of polyvinyl pyridine to Fe(NO3)3·9H2O is 1-1.5 g: 3-5 mmol; The mass ratio of Fe3C@C precursor and elemental sulfur is 1:3-1:5; the heating temperature is 200-500 °C, and the time is 2-5 hours.

2. According to the preparation method of the double-layer coated sulfide positive electrode composite material according to claim 1, the calcination temperature is 600-900 ° C and the time is 1-3 hours.

3. The method for preparing the double-layer coated sulfide positive electrode composite material according to claim 1, characterized in that: In step 3, the mass ratio of FeS2@C nanomaterial to sulfide electrolyte raw material is 8-9:1-2; the sulfide electrolyte raw material is composed of Li2S, P2S5, and LiX in a molar ratio of 5:1:2, and X is one of F, Cl, Br, and I.

4. The method for preparing the double-layer coated sulfide positive electrode composite material according to claim 1, characterized in that: In step 3, the calcination temperature is 200-500 °C and the time is 1-2 h.

5. Use of the double-layer coated sulfide positive electrode composite material obtained by the preparation method as claimed in claim 1 in preparing a sulfide all-solid-state battery positive electrode.

Citation Information

Patent Citations

  • Preparation method of solid electrolyte membrane coated FeS2 / carbon positive electrode material

    CN112397692A

  • Composite positive electrode material, battery positive electrode, lithium battery and application thereof

    CN114824192A